Relationship between entrepreneurial intentions and entrepreneurial career choice behavior among university students - Norasmah Othman; Nor Hafiza Othman (2015)
This study aims to examine the relationship between entrepreneurial intentions and entrepreneurial career choice behavior among Malaysian university students. The sample consists of 469 students in their final year at several Malaysian research universities. A questionnaire was administered to these students to assess their entrepreneurial intentions and entrepreneurial career choice behavior. Finding showed that both entrepreneurial intention and entrepreneurial career choice behavior were at average levels among students. In addition, they indicated a positive significant relationship between entrepreneurial intention and entrepreneurial career choice behavior: higher intention to pursue an entrepreneurship career makes a person more likely to engage in entrepreneurial activities. These findings suggest that the Malaysian Ministry of Higher Education and government agencies in Malaysia should assess and identify the strengths and abilities of graduates before they are accepted into entrepreneurial training and programs. This will ensure that a high percentage of graduates actually become entrepreneurs, and thus will increase the efficiency of entrepreneurial training.